CTNI-33. METRONOMIC TEMOZOLOMIDE THERAPY IN HEAVILY PRETREATED PATIENTS WITH RECURRENT GLIOBLASTOMA: A LARGE MONO-INSTITUTIONAL RETROSPECTIVE STUDY. (12th November 2021) - Bosio, Alberto; Cerretti, Giulia; Padovan, Marta; Caccese, Mario; Guarneri, Valentina; Zagonel, Vittorina; Lombardi, Giuseppe
Abstract: BACKGROUND: Despite advances in surgical and first-line treatment, all glioblastoma pts relapse. The aim of this study is to evaluate the benefit of metronomic temozolomide (mTMZ) for recurrent glioblastoma. METHODS: 120 pts treated at Veneto Institute of Oncology from September 2013 to March 2021 were retrospectively reviewed. Major inclusion criteria were: first-line therapy with Stupp protocol, relapse after first or subsequent line of therapy, treatment with mTMZ schedule (50mg/m 2 continuously), hystologically confirmed diagnosis. RESULTS: mFollow-up was 15.6ms, mAge 59ys (range 18-81), ECOG PS 0-2 in 107pts (89%) and 3 in 11 (9%). MGMT was methylated in 66 of 105 (62%) evaluable pts, IDH mutated in 9 of 106 (8%). mNumber of prior lines of treatment was 2 (range 1-7); 41% of pts received mTMZ beyond the third line. mTime between last standard TMZ (sTMZ) cycle and mTMZ administration was 6ms (range 1-50); 40% of pts started mTMZ after 3ms from sTMZ. All pts were evaluable for response: 3 (2%) and 48 (40%) showed PR and SD. mOS from the start of mTMZ was 5.4ms (95% CI 4.3-6.4), mPFS 2.6ms (95% CI 2.3-2.8). On univariate analysis, MGMTmet and MGMTunmet pts had a mOS of 5.6 and 4.4ms (p= 0.03); mOS for pts with ECOG PS > or ≤ 2 was 2.3 and 6.0ms (p< 0.001). On multivariate analysis, MGMTmet status (HR= 2.3, 95% CI, p= 0.004) and ECOG PS (HR= 0.5, 95% CI, p= 0.017) remained significant for PFS; ECOG PS (HR= 0.4, 95% CI, p= 0.001) was the only factor significantly associated with OS. The most common grade 3-4 hematologic toxicities were lymphopenia (10%) and thrombocytopenia (3%). Grade 3-4 nonhematologic toxicities were uncommon. CONCLUSIONS: Rechallenge with mTMZ can be a well tolerated treatment option for recurrent glioblastoma, even in heavily pretreated pts. Pts with MGMTmet and good ECOG PS might report the major benefit.